2 | − | ( | x | + | 5 | ) | ÷ | 6 | = | x | − | ( | x | − | 1 | ) | ÷ | 3 |
Left side of the equation = | 2 | − | x | × | 1 6 | − | 5 | × | 1 6 |
= | 2 | − | x | × | 1 6 | − | 5 6 |
= | 7 6 | − | 1 6 | x |
7 6 | − | 1 6 | x | = | x | − | ( | x | − | 1 | ) | ÷ | 3 |
Right side of the equation = | x | − | x | × | 1 3 | + | 1 | × | 1 3 |
= | x | − | x | × | 1 3 | + | 1 3 |
= | 2 3 | x | + | 1 3 |
7 6 | − | 1 6 | x | = | 2 3 | x | + | 1 3 |
- | 1 6 | x | − | 2 3 | x | = | 1 3 | − | 7 6 |
- | 5 6 | x | = | 1 3 | − | 7 6 |
- | 5 6 | x | = | - | 5 6 |
5 6 | = | 5 6 | x |
5 6 | x | = | 5 6 |
x | = | 5 6 | ÷ | 5 6 |
= | 5 6 | × | 6 5 |
= | 1 | × | 1 |
x | = | 1 |